PENGARUH ACCOUNTING CONSERVATISM DAN RISK SERTA FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Santoso Chandra; Claudia (E-Jurnal Akuntansi TSM, 2022)
This study was initiated with the aim of knowing several factors that can affect earnings management practices in non-financial companies in Indonesia. These factors are company characteristics which are represented by growth, size, risk, leverage, profitability, accounting conservatism, institutional ownership, and managerial ownership. This study applies the modified Jones model to estimate the value of discretionary accruals. The sample of this study is 100 non-financial companies listed on the Indonesia Stock Exchange from 2018 to 2020 which were obtained through the purposive sampling method. The relationship between company characteristics and earnings management is determined using the multiple regression model. The results of this study indicate that the variables of growth, leverage, and accounting conservatism affect the value of earnings management, while the variables of size, risk, profitability, institutional ownership, and managerial ownership do not show any effect on earnings management